2008
DOI: 10.1371/journal.pone.0003207
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Flexibility: Genetic Variation, Genetic Costs and Long-Term Evolution in a Collembola

Abstract: In a variable yet predictable world, organisms may use environmental cues to make adaptive adjustments to their phenotype. Such phenotypic flexibility is expected commonly to evolve in life history traits, which are closely tied to Darwinian fitness. Yet adaptive life history flexibility remains poorly documented. Here we introduce the collembolan Folsomia candida, a soil-dweller, parthenogenetic (all-female) microarthropod, as a model organism to study the phenotypic expression, genetic variation, fitness con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 84 publications
7
67
1
Order By: Relevance
“…For each springtail species, species code, feeding traits (sucker/shredder), reproduction traits (standard, standard-to-explosive, explosive, parthenogenesis), vertical distribution according to Gisin (1943), and total count in the soil samples are shown in Table 3 (Hopkin, 1997). The determining of springtail reproduction modes was performed from work of Czarnetzki and Tebbe (2004) and Tully and Ferriere (2008). The diet of springtails (sucker/shredder) was defined from the shape of the mouthparts notably maxillar (Chen et al, 1997;Santorufo et al, 2014aSantorufo et al, , 2014bHoskins et al, 2015).…”
Section: Microarthropod Extraction and Identificationmentioning
confidence: 99%
“…For each springtail species, species code, feeding traits (sucker/shredder), reproduction traits (standard, standard-to-explosive, explosive, parthenogenesis), vertical distribution according to Gisin (1943), and total count in the soil samples are shown in Table 3 (Hopkin, 1997). The determining of springtail reproduction modes was performed from work of Czarnetzki and Tebbe (2004) and Tully and Ferriere (2008). The diet of springtails (sucker/shredder) was defined from the shape of the mouthparts notably maxillar (Chen et al, 1997;Santorufo et al, 2014aSantorufo et al, , 2014bHoskins et al, 2015).…”
Section: Microarthropod Extraction and Identificationmentioning
confidence: 99%
“…Probably, as a consequence of accommodation to food, our collembolans in BtBt treatment produced larger eggs than in IsoIso one. Tully and Ferrière (2008) found that there is a positive relationship between egg size and juvenile size, and larger F. candida juveniles have improved quality, which means a higher chance to survive and better productivity. Maybe that is why the time until the first http://www.aloki.hu • clutch is shorter (although not significantly) and the body growth rate is higher in BtBt treatment and BtBt collembolans reach their maturity earlier.…”
Section: Discussionmentioning
confidence: 97%
“…From the ecotoxicological point of view, the egg number decreases due to the effect of heavy metal contamination (Fountain and Hopkin, 2001;Smit et al, 2004). If evolution biology of F. candida was in the focus of the study, difference between clonal lines (Stam, Leemkule and Ernsting, 1996), life-history traits (Tully and Ferrière, 2008;Hafer et al, 2011), or Wolbachia symbiont presence (Timmermans and Ellers, 2009) were studied. Other parameters as the egg shape, the egg viability, and the egg size are rather involved in ecological and evolution biological studies not in ecotoxicological ones (Stam, Leemkule and Ernsting, 1996;Tully and Ferrière, 2008;Timmermans and Ellers, 2009;Hafer and Pike, 2010;Hafer et al, 2011).…”
Section: Folsomia Candidamentioning
confidence: 99%
“…If evolution biology of F. candida was in the focus of the study, difference between clonal lines (Stam, Leemkule and Ernsting, 1996), life-history traits (Tully and Ferrière, 2008;Hafer et al, 2011), or Wolbachia symbiont presence (Timmermans and Ellers, 2009) were studied. Other parameters as the egg shape, the egg viability, and the egg size are rather involved in ecological and evolution biological studies not in ecotoxicological ones (Stam, Leemkule and Ernsting, 1996;Tully and Ferrière, 2008;Timmermans and Ellers, 2009;Hafer and Pike, 2010;Hafer et al, 2011). For example, Tully and Ferrière (2008) measured egg size, egg number, clutch size and clutch number to reveal the different life-history strategies of F. candida reacting to different food availability and overcrowding.…”
Section: Folsomia Candidamentioning
confidence: 99%
See 1 more Smart Citation